Synthesis and preliminary cytotoxicity study of a cephalosporin-CC-1065 analogue prodrug - Wang, Yuqiang (BioMed Central, 2001)
BACKGROUND: Antibody-directed enzyme prodrug therapy (ADEPT) is a promising new approach to deliver anticancer drugs selectively to tumor cells. In this approach, an enzyme is conjugated to a tumor-specific antibody. The antibody selectively localizes the enzyme to the tumor cell surface. Subsequent administration of a prodrug substrate of the enzyme leads to the enzyme-catalyzed release of the free drug at the tumor site. The free drug will destroy the tumor cells selectively, thus, reducing side effects. RESULTS: A CC-1065 analogue was conjugated to a cephalosporin affording prodrug 2. The prodrug and its corresponding free drug, 1, have IC(50) values of 0.9 and 0.09 nM, respectively, against U937 leukemia cells in vitro. CONCLUSIONS: For the first time, a prodrug comprised of a cephalosporin and a CC-1065 analogue has been synthesized. The preliminary in vitro studies show that the prodrug was 10-fold less toxic than the free drug. Prodrug 2 has the potential to be useful in cancer treatment using the ADEPT approach.